Use of Simini Protect Lavage as an Adjuvant in the Antiseptic Protocol for Revision Surgeries Involving Total Hip Replacement - Forzisi, Ida; Vezzoni, Luca; Bozzerla, Milo; Vezzoni, Aldo (VCOT Open, 2025)
Objectives Despite advances in surgical asepsis and improvements in sterile surgical techniques, surgical site infection occurs in 0.8 to 15.8% of surgical wounds. Most infections are caused by microorganisms forming biofilms that adhere to implants or dead bone and can evade host immunity and antimicrobial agents. Simini Protect Lavage (SPL) is a hypertonic aqueous solution designed to break cross-links within the extracellular polymeric substance of biofilms produced by bacteria. This study aimed to report the outcome of our total hip replacement (THR) revision cases using an SPL in addition to our standard antiseptic protocol.Methods The medical records of patients at Vezzoni Veterinary Clinic were searched for animals undergoing a revision orthopaedic surgery involving a THR that included the use of SPL. In all patients, a minimum of 1-year follow-up and culture and a sensitivity test pre- and post-Simini Lavage were required.Results SPL was used in 36 cases. At the beginning of surgery, culture and sensitive tests were positive in eight patients, and at the end of surgery, seven dogs were still positive for bacterial infection. Only one case, which experienced three revision surgeries, underwent explantation due to persistent, clinically evident infection. The other dogs showed neither clinical nor X-ray signs of infection over a long period.Clinical Significance The use of SPL can be considered as an adjuvant in the antiseptic protocol for the one-stage revision THR surgeries without a plan of prosthesis explanation. Nevertheless, further studies are needed to objectively evaluate the efficacy of SPL in eradicating the postoperative infections.
Keywords: infections; surgical site infection; revision surgery; intraoperative antiseptic lavage